Electricity from wave and tide : an introduction to marine energy - Lynn, Paul A. (John Wiley & Sons Inc., 2014)
"A concise yet technically authoritative overview of modern marine energy devices with the goal of sustainable electricity generation With 165 full-colour illustrations and photographs of devices at an advanced stage, the book provides inspiring case studies of today's most promising marine energy devices and developments, including full-scale grid-connected prototypes tested in sea conditions. It also covers the European Marine Energy Centre (EMEC) in Orkney, Scotland, where many of the devices are assessed.Topics discussed: global resources - drawing energy from the World's waves and tides history of wave and tidal stream systems theoretical background to modern developments conversion of marine energy into grid electricity modern wave energy converters and tidal stream energy converters This book is aimed at a wide readership including professionals, policy makers and employees in the energy sector needing an introduction to marine energy. Its descriptive style and technical level will also appeal to students of renewable energy, and the growing number of people who wish to understand how marine devices can contribute to carbon-free electricity generation in the 21st century"--